The effects of cognitive general imagery training on decision-making abilities in curling: A single-subject multiple baseline approach - Westlund Stewart, N.; Hall, C. (Journal of Applied Sport Psychology, 2017)
A single-subject multiple baseline design was used to assess the effects of cognitive general imagery training on the strategy performance of three curlers (Mage = 19.33, SD = 3.06) over 18 weeks. Visual and statistical analyses (i.e., response accuracy and response time) revealed that one curler improved her response accuracy and two curlers decreased their response time. These findings provide support for individual responses to the intervention, which may have been missed by a group-level analysis (Hrycaiko & Martin, 1996 Hrycaiko, D., & Martin, G.L. (1996). Applied research studies with single-subject designs: Why so few? Journal of Applied Sport Psychology, 8, 183-199.[Taylor & Francis Online], [Web of Science ®], , [Google Scholar]). These findings extend the literature by showing that a cognitive general imagery intervention can improve strategy performance in curling.